2005
DOI: 10.1086/429746
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of Active Galactic Nucleus Outbursts in the Gaseous Atmosphere of M87

Abstract: We combined deep Chandra, ROSAT HRI, and XMM-Newton observations of M87 to study the impact of AGN outbursts on its gaseous atmosphere. Many X-ray features appear to be a direct result of repetitive AGN outbursts. In particular, the X-ray cavities around the jet and counter jet are likely due to the expansion of radio plasma, while rings of enhanced emission at 14 and 17 kpc are probably shock fronts associated with outbursts that began 1 − 2 × 10 7 years ago. The effects of these shocks are also seen in brigh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
338
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(367 citation statements)
references
References 59 publications
29
338
0
Order By: Relevance
“…The minimum value of Mach number is along the South direction and it could be due to projection effect, which was also reported earlier (Croston et al 2011). (Forman et al 2005(Forman et al , 2007Million et al 2010). …”
Section: Shocks In Icmsupporting
confidence: 82%
“…The minimum value of Mach number is along the South direction and it could be due to projection effect, which was also reported earlier (Croston et al 2011). (Forman et al 2005(Forman et al , 2007Million et al 2010). …”
Section: Shocks In Icmsupporting
confidence: 82%
“…I here concentrate on results from the last five years. Randall et al (2011) and Randall et al (2015) argue, based on their X-ray observations and analysis of the galaxy group NGC 5813, that shocks excited by periodic jets activity heat the ICM (for early studies of shocks in the Virgo cluster see Forman et al 2005 andForman et al 2007). This heating mechanism is put into question by Soker et al (2016).…”
Section: Heating the Icmmentioning
confidence: 99%
“…Ascasibar & Markevitch 2006, Roediger et al 2011, ZuHone et al 2011, Johnson et al 2012, Simionescu et al 2012, Paterno-Mahler et al 2013, cavities (e.g. Fabian et al 2000, 2003, McNamara et al 2000, Forman et al 2005, Hlavacek-Larrondo et al 2012; see also reviews by McNamara et al 2000 andFabian 2012), and the cool, dense cores found in some clusters (e.g. Fabian et al 1994, White et al 1997, Peres et al 1998, Peterson & Fabian 2006.…”
Section: Introductionmentioning
confidence: 99%